Systematic Literature Review : Model Pembelajaran Discovery Learning Untuk Meningkatkan Kemampuan Numerasi Siswa Sekolah Menengah Pertama - Ulfa, Komaria; Fauziah, Anna; Ningrum Mawardi, Dona (STAI Al-Bahjah, 2025)
This study aims to systematically review various research results related to the use of the Discovery Learning learning model in improving students' numeracy skills. The method used is the Systematic Literature Review (SLR) by tracing and analyzing relevant scientific articles from various trusted sources. The results of the study show that the application of the Discovery Learning model consistently can improve students' numeracy skills. This model encourages students to actively build their own understanding, make connections between mathematical ideas, and foster deep and lasting understanding. In addition, numeracy learning that is fun and meaningful has proven to be more interesting for students and supports optimal numeracy skills. Thus, Discovery Learning is recommended as an alternative learning model that is effective in strengthening numeracy literacy at various levels of education.